2008
DOI: 10.1007/s10573-008-0080-3
|View full text |Cite
|
Sign up to set email alerts
|

Transitional regimes of wave propagation in metastable systems

Abstract: Results of a theoretical study of deflagration-to-detonation transition processes in hydrogen-air mixtures are presented. The dependence of the deflagration-todetonation transition scenario on the governing parameters (initial temperature of the mixture, ignition energy, ignition time, geometric characteristics of cavities, and distances between cavities in the ignition zone) is considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The validation of the numerical model was performed by comparing the cell size numerically obtained for the stoichiometric hydrogen-air mixture using different kinetic mechanisms with the results of experimental measurements obtained by different authors [35,36]. The instability of the leading shock wave was also verified by studying dispersed-film and other metastable systems [37,38].…”
Section: Numerical Modelmentioning
confidence: 99%
“…The validation of the numerical model was performed by comparing the cell size numerically obtained for the stoichiometric hydrogen-air mixture using different kinetic mechanisms with the results of experimental measurements obtained by different authors [35,36]. The instability of the leading shock wave was also verified by studying dispersed-film and other metastable systems [37,38].…”
Section: Numerical Modelmentioning
confidence: 99%
“…In most cases, the turbulent transport supersedes the molecular, and the last is made using simplified technique using constant Prandtl Pr and Schmidt Sc numbers hypothesis [13]:…”
Section: Turbulence Model and Transportmentioning
confidence: 99%
“…It has been reported that cavities can help realize detonation initiation through the DDT mechanism, and an increase in the number of cavities promotes DDT as long as the flame velocity leaving the last cavity does not exceed the sonic velocity [69] [70] .…”
Section: Cavity-based Initiationmentioning
confidence: 99%